WOMEN'S REPRODUCTIVE RIGHTS AND THEIR PROTECTION ISSUES - Axmedova Sayyora Muxammadovna; Rahmonova Umida Tohir qizi; Abdumannonova Xidoyatxon Ganisher qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Women's reproductive rights ensure their health, enable control over pregnancy, provide freedom of reproductive choice, and access to preventive medical services. This article analyzes the concept of reproductive rights, mechanisms of their protection, legal and medical frameworks, as well as contemporary global and Uzbek practices. The importance of preventive examinations, reproductive health programs, and legal mechanisms is highlighted